Modeling the relationship between statistical achievement and cognitive determinants among Malaysian diploma students / Foo Kien Kheng - Foo , Kien Kheng (2017)
The main purpose of the study is to determine the relationships of selected cognitive determinants on statistical achievement and statistical reasoning. In addition it seeks to determine the direct and indirect effect of gender and language on these relationships. This study uses a survey approach to collect data on the exogenous and endogenous variables using data from a cross-section of the sample of Diploma students. A survey form was used to collect secondary and primary data. To increase the content and construct validity of the instrument, two pilot studies were carried out. The pilot studies included the use of focus groups. Item analysis was used to weed out poor items. Reliability of the instrument was measured using Cronbach alpha. The SRA has moderately good reliability index. Purposive sampling was used to select 381 students from 6 statistics classes sourced from two branch campuses of a large university in Malaysia. The survey was administered a week later and handed back to the researcher immediately. Data cleaning and screening were carried out and only 374 usable forms were keyed in using the SPSS package. Multiple linear regression (MLR) analytic procedure was used to study the complex multivariate relationships based on the different hypothesized models as suggested in this present study. The findings showed that, students achieved moderately well on prior mathematical knowledge (PMK) and statistical achievement (SA). Unfortunately, they did not do well in statistical reasoning (SR) and had a substantially high level of misconception (MC) about statistics. PMK (M = 78.54, SD = 11.72) and SA (M = 64.63, SD = 24.78) as compared to SR (M= 38.17, SD = 13.83) and MC (M = 34.44, SD = 11.56). The best regression model on statistical achievement was: SA =8.75+.58 (PMK) + .27(SR) where only prior mathematical knowledge (PMK) and statistical reasoning (SR) being significant contributors. The best model on statistical reasoning was: SR=43.61+0.05(SA)−0.58(MC)+3.45(ENG) where SA, MC and ENG were significant contributors to SR. Finally the findings found that gender and language mastery did not moderate the hypothesized relationships among the various cognitive determinants on achievement or reasoning. The significance of the findings includes identifying the determinants that are directly or indirectly influencing achievement and reasoning. These are important input for educators to find ways to improve the teaching and learning process in class. The current study has also shown that statistical achievement and reasoning are complex constructs and that the determinants used are but a small subset of the population of cognitive and non-cognitive factors.